Depois de Freud: “O Que é o homem?” Dramática humana e o Mal-Estar na Civilização - Bastos, José Gabriel Pereira (Trabalhos de Antropologia e Etnologia, 2020)
Freud has altered the premises of comprehension of the human as well as of the historical development of the Men in the world, which were philosophical, by postulating an entirely new way of speaking about the human kind. Freud demands a new type of science, transversal and integrative (i.e., against discipline compartments, non Academic, and no merely digressive and scholarly), which can examine the articulation of an unstable and delusional Mind with the dramatical and problematic organization of the Political World. This new way of doing science aims to equate the paradox of “Civilization and its Discontents”, which Social Darwinism, centered in the concept of Civilizational Progress, was not able to study, except to propose its overcoming (from Hitler to Bertrand Russell) with an overbearing and delusional ‘Real Politik.’